2000
DOI: 10.1002/(sici)1521-3773(20000515)39:10<1821::aid-anie1821>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Fully Reversible Cyclic Dimerization of Diphosphanylketenimines Promoted by Intramolecular C−H⋅⋅⋅N Hydrogen Bonds

Abstract: Just by crystallization at room temperature the diphosphanylketenimine 1 is transformed into the unsymmetrical dimer 2 through a novel [2+3] cycloaddition reaction; a phosphanyl substituent is involved in the annelation process. This dimerization is fully reversible and appears to be promoted by intramolecular CH⋅⋅⋅N hydrogen bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Fortunately, the suitability of 3 to undergo reversible cyclic dimerization allowed us to obtain 8 in a pure form. As we have recently communicated,6 the diphosphanylketenimine 3 dimerizes upon crystallization giving the unsymmetrical dimer 6 (Scheme ), which quantitatively reverts to 3 on heating with toluene. The three trivalent phosphorus atoms in 6 can be selectively oxidized by treatment with one, two or three equivalents of H 2 O 2 giving 7, 9 , and the transient species 10 , respectively (Scheme ).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Fortunately, the suitability of 3 to undergo reversible cyclic dimerization allowed us to obtain 8 in a pure form. As we have recently communicated,6 the diphosphanylketenimine 3 dimerizes upon crystallization giving the unsymmetrical dimer 6 (Scheme ), which quantitatively reverts to 3 on heating with toluene. The three trivalent phosphorus atoms in 6 can be selectively oxidized by treatment with one, two or three equivalents of H 2 O 2 giving 7, 9 , and the transient species 10 , respectively (Scheme ).…”
Section: Resultsmentioning
confidence: 85%
“…Chemical shifts are given in ppm, relative to internal SiMe 4 ( 1 H) or external 85 % H 3 PO 4 ( 31 P). The compounds 3 5 and 6 6 were prepared as described elsewhere. All other reagents were commercially obtained and used without further purification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reversible cyclic dimerisation of diphosphanylketenimines (Ph 2 P) 2 CNCNNPh involving a [2 + 3] cycloaddition has been observed to give an azaphospha heterocycle 14 featuring a phosphorus ylide functionality. 72 Dimerisation appears to be promoted by C-H•••N hydrogen bond formation.…”
Section: Phosphorusmentioning
confidence: 99%
“…These calculations suggest that the [NN–P] moiety of 1 could behave as a 1,3-dipole, consistent with the rapid reaction between 1 and cyclooctyne. Although 1,3-(P,C) dipole reactivity is known, 1,3-dipolar cycloadditions involving 1,3-(P,N) dipoles are rare. In one example, Swarmy and co-workers found that the treatment of 2 equiv of azide-substituted phosphine with dipolarophile dimethylacetylene dicarboxylate (DMAD) results in the formation of a 1,3-(P,N) heterocycle containing an appended phosphazenyl azide unit …”
mentioning
confidence: 99%